Fingolimod and CSF neurofilament light chain levels in relapsing-remitting multiple sclerosis - Kuhle, Jens (Neurology, 2015)
OBJECTIVE: We assessed CSF levels of the light chain subunit of neurofilaments (NfL) at baseline and after fingolimod therapy or placebo in patients with relapsing-remitting multiple sclerosis (RRMS). Changes in NfL levels were also correlated with relapse and MRI outcomes. METHODS: CSF samples were available, at baseline and 12 months after treatment initiation, from a subset of 36 patients with RRMS (fingolimod 0.5 mg: n = 9; fingolimod 1.25 mg: n = 15; placebo: n = 12) participating in the 2-year, phase 3 Fingolimod (FTY720) Research Evaluating Effects of Daily Oral Therapy in Multiple Sclerosis (FREEDOMS) study. NfL levels were determined in a blinded fashion using a commercial ELISA kit. RESULTS: Median NfL levels did not differ between treatment groups at baseline (0.5 mg: 644 pg/mL; 1.25 mg: 659 pg/mL; pooled 0.5/1.25 mg: 652 pg/mL, placebo: 886 pg/mL; p value [fingolimod vs placebo] = 0.619, 0.495, and 0.481, respectively). Following 12 months of treatment, median changes from baseline in NfL levels were lower than zero in the fingolimod groups (0.5 mg: −346 pg/mL, p = 0.039; 1.25 mg: −313 pg/mL, p = 0.035) and pooled 0.5/1.25 mg fingolimod group (−326 pg/mL, 83.3% with reduction, p = 0.002) but not in the placebo group (−214 pg/mL, 66.7% with reduction, p = 0.388). Reductions in NfL levels at month 12 correlated with an improvement in relapse and MRI outcomes. CONCLUSIONS: Our results suggest a beneficial effect of fingolimod on this marker of axonal injury and support the utility of NfL as a quantitative biomarker in multiple sclerosis.